A customizable controller for 3 axis modular CNC machine - Jagathesvaran, Veeramony; M. Nafis, O. Z. (Penerbit UMP, 2022)
Numerical control is a useful technology to control a machine that utilize numeric values and codes. The machine comes with various sizes and built-in with its own controller. However, most of the commercial CNCs controllers are expensive and work only on the dedicated machine. With recent advancement of automation, a custom conrtoller for CN machine operation is possibly to be build. In this project, the three axis motion is controlled by Arduino Uno board with Atmega 328p microcontroller. In this case, the Arduino serves as an open source burner that burns the microcontroller using the provided programmes. Stepper motor drivers and the CNC shield accept signals from the Arduino board and transmit power to the stepper motors. Using Inkspace software, the user must first convert any image or text file into G-code before feeding it to the machine. The G-code file is then browsed in Universal G-code Sender software connected to a GRBL shield v0.9i and Arduino board through a laptop serial interface. The Universal G-code Sender programme has a G-code visualizer feature that allows to see the manufacturing processes alongside the simulation.